Effect of Sodium Tanshinone IIA Sulfonate Injection on Blood Lipid in Patients With Coronary Heart Disease: A Systematic Review and Meta-Analysis of Randomized Clinical Trials - Zhou, Hufang; Zhao, Ying; Peng, Wenhua; Han, Wenbo; Wang, Zichen; Ren, Xiaoxia; Wang, Dayang; Pan, Guozhong; Lin, Qian; Wang, Xian (Frontiers in Cardiovascular Medicine, 2021)
Background: Lipid-lowering therapy is very important in secondary prevention of coronary heart disease (CHD). In many clinical trials, it has been found that Sodium Tanshinone IIA Sulfonate Injection (STS) have a lipid-lowering effect while reducing major cardiovascular events in patients with CHD. However, up to now, there is no system review on the effectiveness and safety of STS affecting blood lipids. Purpose: The aim of this review is to systematically assess the effects of STS on blood lipid levels in patients with CHD. Methods: Until Mar 2021, five databases (PubMed, EMBASE, Cochrane Library, China National Knowledge Infrastructure, and Wanfang Database) were searched for randomized controlled trials (RCTs) about STS treating patients with CHD. Risk bias was assessed for included studies according to Cochrane handbook. The primary outcome was total cholesterol (TC). The secondary outcomes were triglycerides (TG), low-density lipoprotein cholesterol (LDL-c), high-density lipoprotein cholesterol (HDL-c), and adverse events (AEs). Results: A total of 27 trials including 2445 CHD patients met the eligibility criteria. Most trials had high risks in random sequence generation, allocation concealment, blinding of patients and personal, blinding of outcome assessment. Meta-analysis showed that STS significantly reduced plasma TC levels (MD = −1.34 mmol/l 95% CI [−1.59, −1.09], p < 0.00001, I2 = 98%), TG levels (MD = −0.49 mmol/l 95% CI [−0.62, −0.35], p < 0.00001, I2 = 97%), LDL-c levels (MD = −0.68 mmol/l [−0.80, −0.57], p < 0.00001, I2 = 96%), increased HDL-c levels (MD =0.26 mmol/l [0.15, 0.37], p < 0.00001, I2 = 97%), without increasing the incidence of AEs (RR = 1.27 95% CI [0.72,2.27], p = 0.94, I2 = 0%) in patients with CHD. Conclusion: STS can safely and effectively reduce plasma TC, TG and LDL-c levels in patients with CHD, and improve plasma HDL-c levels. However, due to the low overall quality of RCTs at present, the above conclusions need to be verified in larger samples of high-quality research.